(untitled) (Clinics, 2006)
PURPOSE: To evaluate 20 cases of nonmetastatic synovial sarcoma of the extremities regarding prognostic factors, and to propose a histologic grading system with prognostic significance. METHODS: The cases of 20 patients (14 females and 6 males) with nonmetastatic synovial sarcomas of the extremities treated between 1985 and 1998, were retrospectively evaluated regarding prognostic factors. A histologic grading system with prognostic significance is proposed. RESULTS: The mean follow-up period was 48.4 months (range, 16-116 months). There was local recurrence in 3 cases (15%), microscopic surgical margin being the only prognostic factor identified. Seven patients (35%) died of the disease in a mean postoperative period of 31.7 months (range, 16-53 months), all with pulmonary or brain metastasis. The survival rate was 65% in 48.4 months of follow-up. CONCLUSION: The unfavorable prognostic factors identified regarding survival were high histologic grade, tumors proximal to the knee or elbow, and spontaneous tumor necrosis over 25%. Local recurrence did not have influence on survival in this study. The presence of mast cells appears to have a positive influence on survival, although statistical significance was not reached (P = 0.07). The oncologic and functional result was good in 6 cases (30%), regular in 7 (35%), and poor in 7 cases (35%).